DAMPAK KEUANGAN SYARIAH PADA KETAHANAN EKONOMI DI MASA PANDEMI - Mutiari, Pury Sunita; K, Kamilah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2025)
The COVID-19 pandemic has had a major impact on the global economy, including in Indonesia. Economic resilience is a crucial issue in dealing with this uncertainty. One of the sectors of concern is the financial sector, especially Islamic finance which is expected to provide alternative solutions. This study aims to analyze the impact of Islamic finance on economic resilience during a pandemic. The method used in this research is qualitative analysis with a case study approach to Islamic financial institutions in Indonesia. The results of this study are expected to provide a clearer picture of the role of Islamic finance in supporting economic resilience during the pandemic.